Brand Value Co-Creation and Brand Evangelism : A Study on Sustainable Skincare Products - Mujahid, Simra; Khandai, Sujata; Venkatesh, Umashankar (Indian Journal of Marketing, 2025)
Purpose : The objective of the current research was to examine the impact of brand value co-creation on brand evangelism with an emphasis on the serial mediating roles of brand love and brand commitment. As customers became more participatory and value-oriented, understanding how co-creation transformed emotional attachment into advocacy behaviour became crucial for sustainable brand growth. Methodology : Data were gathered through an online structured questionnaire administered to Indian consumers who were aware of sustainable cosmetic brands. The study followed a descriptive and cross-sectional research design. A total of 368 valid responses were obtained, and the proposed framework was tested using AMOS 24 and SPSS 26. Findings : The analysis confirmed the presence of a serial mediation process. Brand value co-creation positively affected brand evangelism, and this relationship operated through brand love and brand commitment. The results suggested that when consumers participated in co-creation activities, they developed a stronger emotional attachment and a deeper sense of commitment, which together prompted them to promote the brand enthusiastically. Practical Implications : The study highlighted the importance of designing co-creation strategies that nurtured brand love and commitment. Managers were encouraged to promote authentic consumer participation and transparent communication to cultivate emotional engagement, strengthen commitment, and convert satisfied customers into active brand evangelists. Originality : This research expanded the service-dominant logic by empirically confirming a serial mediation model that connected brand value co-creation, brand love, brand commitment, and brand evangelism within the sustainable cosmetics sector, which has been scarcely studied academically.